Experiments with heat - Tocci, Salvatore; Rasch, Patricia (New York Children's Press, 2002)
Presents experiments that introduce and explain the concept of heat
Includes bibliographical references (p. 44) and index
Hurg
5
Keywords: Experiments; Heat -- Experiments